Avaliação da eficácia do tratamento nutricional oferecido pelo SUS para portadores de NASH - Silva, Giovanna Zanelli (2015)
Introduction: Nonalcoholic Fatty Liver Disease (NAFLD) is characterized by an increase in intracellular content of triglycerides; its prevalence worldwidely is nearly 20-30% of the population. This disease has spectral nature that includes steatosis and nonalcoholic steatohepatitis (NASH) in the absence of significant alcohol consumption. Although NAFLD may remain as a stable disease for longer periods, this condition may progress to advanced stages of cirrhosis and liver cancer. Diabetes Mellitus Type 2, insulin resistance and obesity are important risk factors, among others, for development of NAFLD, and are directly related to sedentary lifestyle and inappropriate eating habits. Thus, alteration in lifestyle, changes in eating habits and regular physical activity play a fundamental role in treating this disease. Aim: To evaluate the effectiveness of hypocaloric diet for the treatment of NASH as well as adherence to treatment. Methods: This is a prospective longitudinal open cohort study, in which 26 NASH patients were divided into 2 group: 15 patients in the control group and 11 patients in the treatment group which were followed up for 6 months. Both groups were diagnosed by liver biopsy. The treatment group was a given lifestyle change program with supervised low-calorie diet (20-25 kcal / kg actual weight / day), monitored exercise, standard treatment of metabolic syndrome and drug maintenance treatment with metformin and N- acetylcysteine. The control group received general guidelines on diet and weight loss, encouragement to practice physical exercise, standard treatment of metabolic syndrome and maintenance of drug treatment with metformin. Criteria for inclusion: patients with at least one of the component of metabolic syndrome; BMI ≥ 25 and ≤ 40 kg /m² and sedentary for at least three months. Criteria for exclusion: other concomitant liver diseases, alcohol intake greater than or equal to 21 drinks / week, or 140 g / day for men and 14 drinks / week or 70g / day for women, medication known to be associated with NAFLD, untreated hypothyroidism or hyperthyroidism, previous bariatric surgery, or uncontrolled psychiatric disorder. Diagnostic criteria: the diagnosis of NASH was done by liver biopsy in patients with steatosis on ultrasound or MRI and at least one risk factor for advanced fibrosis into the period up to one year before entering the study. The lifestyle change program in the treatment group had a weight loss goal of 5% or more of their initial weight within six months. Evaluation criteria: a monthly basis applied the clinical evaluation protocol and on a quarterly basis the laboratorial, according to the following variables: weight, height, body mass index, waist circumference, hip circumference, aminotransferase levels, gamma GT, total cholesterol and fractions, triglycerides. Statistical analysis: the descriptive variables were expressed as frequency, mean or median, standard deviation and variation as applicable. The Student t test and Mann-Whitney test were used for comparative analysis. It was admitted confidence interval of 95% and a significance level of P <0.05. Results: Of the 15 patients enrolled with a diagnosis of NASH who were submitted to nutritional treatment, 12 patients completed the six month follow-up of the study. The average age was 51.42 years ± 8.50, being 08 (66%) women and 04 (33%) men. Of this total, only one patient refused to carry out physical activity. Two (17%) among the 12 participants who completed the six month follow-up reached the percentage of expected weight loss. The average percentage of adaptation to the proposed diet was 82.93% ± 13.51%. Conclusion: The lifestyle change program tested for six months associated with NASH treatment, was not effective for clinical and biochemical improvement even with satisfactory adherence by most patients. Our data point out to the potential role of more restrictive diets and intensive supervision in this context combined with multidisciplinary team for the treatment of NASH. This real-life study produced crucial information for readjustment of the multidisciplinary treatment protocol for patients followed up in the service.